Maternal and larval niche construction interact to shape development, survival, and population divergence in the dung beetle Onthophagus taurus. Issue 5 (16th August 2020) - Dury, Guillaume J.; Moczek, Armin P.; Schwab, Daniel B.
Abstract: Through niche construction, organisms modify their environments in ways that can alter how selection acts on themselves and their offspring. However, the role of niche construction in shaping developmental and evolutionary trajectories, and its importance for population divergences and local adaptation, remains largely unclear. In this study, we manipulated both maternal and larval niche construction and measured the effects on fitness‐relevant traits in two rapidly diverging populations of the bull‐headed dung beetle, Onthophagus taurus . We find that both types of niche construction enhance adult size, peak larval mass, and pupal mass, which when compromised lead to a synergistic decrease in survival. Furthermore, for one measure, duration of larval development, we find that the two populations have diverged in their reliance on niche construction: larval niche construction appears to buffer against compromised maternal niche construction only in beetles from Western Australia, but not in beetles from the Eastern United States. We discuss our results in the context of rapid adaptation to novel conditions and the role of niche construction therein. Abstract : We manipulated maternal and larval niche construction (NC) in two populations of beetles. Across populations both NC types enhance fitness‐related traits, synergistically increase survival, but differentially interact to impact larval duration.